Effects of perceived social status and discrimination on hope and empowerment among individuals with serious mental illnesses. (April 2020) - Langlois, Stephanie; Pauselli, Luca; Anderson, Simone; Ashekun, Oluwatoyin; Ellis, Samantha; Graves, JaShala; Zern, Adria; Gaffney, Ebony; Shim, Ruth S.; Compton, Michael T.
Highlights: Hope is decreased by depression, perceived social status, and discrimination. Perceived social status directly impacts hope, and indirectly through depression. Perceived everyday discrimination affects hope through effects on depression. Abstract: Hope and empowerment are key elements of recovery in the context of serious mental illnesses (SMI). We examined predictors of hope among individuals with SMI and tested a hypothesized path model in which perceived social status and perceived discrimination adversely impact hope, directly and through their impacts on depressive symptoms. Data from 232 individuals with SMI receiving care in public-sector settings were used in both a multiple linear regression (predicting Herth Hope Scale scores), and in path analyses examining both direct and indirect effects of perceived social status (Social Status Ladder) and perceived discrimination (Everyday Discrimination Scale). Depressive symptoms, perceived social status, and perceived discrimination were predictive of hope. Path analyses revealed that perceived social status has a direct effect on hope and empowerment but also impacts hope through its effects on depression. Similarly, perceived everyday discrimination affects hope and empowerment, though this effect is mediated through its effects on depression. Two alternative models and a trimmed hypothesized model did not fit the data or improve fit. These social determinants of mental health should provoke program and policy change to improve mental health and enhance recovery among persons with SMI.